Autotransplantation of a Supernumerary Tooth to Replace a Misaligned Incisor with Abnormal Dimensions and Morphology: 2-Year Follow-Up. (11th February 2013) - Tirali, R. Ebru; Sar, Cagla; Ates, Ufuk; Kizilkaya, Metin; Cehreli, S. Burcak
Abstract : Autotransplantation is a viable treatment option to restore esthetics and function impaired by abnormally shaped teeth when a suitable donors tooth is available. This paper describes the autotransplantation and 2-year follow-up of a supernumerary maxillary incisor as a replacement to a misaligned maxillary incisor with abnormal crown morphology and size. The supernumerary incisor was immediately autotransplanted into the extraction site of the large incisor and was stabilized with a bonded semirigid splint for 2 weeks. Fixed orthodontic therapy was initiated 3 months after autotransplantation. Ideal alignment of the incisors was accomplished after 6 months along with radiographic evidence of apical closure and osseous/periodontal regeneration. In autogenous tooth transplantation, a successful clinical outcome can be achieved if the cases are selected and treated properly.